MAKNA KELUARGA BATAK PADA FILM NGERI-NGERI SEDAP - Vika Andriyani; Fakhrur Rozi (Yayasan Pendidikan Islam dan Multikultural, 2022)
Abstract: Film is one of the mass media channels that contains messages from the reality of everyday social phenomena which are then projected onto the screen. Films always record the reality that occurs in the social environment. In order to be more easily accepted, the reality is wrapped in order to be more easily accepted, the reality is wrapped in an interesting picture from a film. Horror Sedap is a family drama film set in a Batak family, which conveys the concerns of overseas children who are bound by customs and culture, which is adapted from the novel of the same name by Bene Dion Rajagukguk. This study aims to describe the meaning of the Batak family in the film Ngeri-Ngeri Sedap based on the meaning of denotation, connotation, and myth. Keywords: Ngeri-Ngeri Sedap, The Meaning of Batak Family, Semiotics Rholand Barthes Abstrak: Film merupakan salah satu saluran media massa yang berisi pesan dari sebuah realitas fenomena sosial sehari-hari untuk kemudian diproyeksikan ke layar kaca. Film selalu merekam kenyataan yang terjadi di lingkungan sosial. Agar lebih mudah di terima maka realitas tersebut dibungkus dengan gambaran yang menarik dari sebuah film. Film Ngeri-Ngeri Sedap merupakan Film Drama Keluarga berlatar keluarga Batak, yang menyampaikan keresahan anak-anak rantau yang terikat dengan adat dan budaya, yang diadaptasi dari novel berjudul sama karya Bene Dion Rajagukguk. Penelitian ini bertujuan untuk menggambarkan makna keluarga batak dalam film Ngeri-Ngeri Sedap berdasarkan makna denotasi, konotasi, serta mitos. Kata kunci: Ngeri-Ngeri Sedap, Makna Keluarga Batak, Semiotika Rholand Barthes